2021
DOI: 10.3390/jpm11121336
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Radiomic Features to Predict Overall Survival Time for Glioblastoma Patients

Abstract: Glioblastoma is an aggressive brain tumor with a low survival rate. Understanding tumor behavior by predicting prognosis outcomes is a crucial factor in deciding a proper treatment plan. In this paper, an automatic overall survival time prediction system (OST) for glioblastoma patients is developed on the basis of radiomic features and machine learning (ML). This system is designed to predict prognosis outcomes by classifying a glioblastoma patient into one of three survival groups: short-term, mid-term, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Various authors focused on the combined use of ML and radiomic techniques for OS prediction in brain tumors [ 92 , 93 ]. Chato et al [ 92 ] focused on GBM, while Grist et al [ 93 ] focused on paediatric brain tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors focused on the combined use of ML and radiomic techniques for OS prediction in brain tumors [ 92 , 93 ]. Chato et al [ 92 ] focused on GBM, while Grist et al [ 93 ] focused on paediatric brain tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Various authors focused on the combined use of ML and radiomic techniques for OS prediction in brain tumors [ 92 , 93 ]. Chato et al [ 92 ] focused on GBM, while Grist et al [ 93 ] focused on paediatric brain tumors. The latter combined multi-site MRI with ML methods to predict survival in paediatric brain tumors, with the aim of stratifying patients to low and high risk cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we assumed that RS could reflect a clinical potential in establishing a connection with MRI images and survival. 33,34 Some articles have indicated that pT and pN are very critical prognostic factors, which are instructive for OS in univariate Cox-regression analysis but not obvious in multivariate Cox-regression analysis. [35][36][37] A possible explanation for this observation was that the patient had underwent gastrectomy to remove the risk factors of the primary tumor, so the effect on the later survival is not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…In the first approach, radiomics features are used for the prediction of survival. Several researchers [14,15,16,17,18,19,20] have used the BraTS dataset for training and evaluation. Deep features combined with radiomic (intensity, texture, wavelet, shape) and clinical information, are initially used, and then those features are input into a random forest regressor [14] to predict overall survival in days.…”
Section: Related Workmentioning
confidence: 99%
“…Another study used 4524 radiomics features and clinical data to train a random forest regressor [16]. Location features were investigated in [17] using a fusion of radiomics, location, and clinical features. A multilayer perceptron (MLP) network was then used for survival prediction using 13 shape features and clinical information [18].…”
Section: Related Workmentioning
confidence: 99%